Mycorrhizal‐mediated plant–herbivore interactions in a high CO2 world. (6th May 2019) - Frew, Adam; Price, Jodi N.
Abstract: The symbiotic relationship between terrestrial plants and arbuscular mycorrhizal (AM) fungi is a key driver of plant nutritional and defence traits influencing insect herbivory. These tripartite interactions have been fundamental to shaping the evolution of land plants and the diversity of insect herbivores. Surprisingly, we have little understanding of how these interactions will function under elevated atmospheric CO2 concentrations (eCO2 ), despite the considerable implications for both natural and managed ecosystems. Although substantial research has revealed how eCO2 alters mycorrhizal–plant interactions, or plant–herbivore interactions, there is a stark scarcity of studies which investigate how eCO2 impacts mycorrhizal‐mediated plant–insect herbivore relationships. Here, we synthesise some of the main effects of eCO2 on the mycorrhizal symbiosis, the concomitant impacts on plant nutrient dynamics and secondary metabolism, and how eCO2 ‐driven changes in plant growth, biochemistry and communities impact insect herbivores. We point out that potential mechanistic drivers of AM fungal–plant–insect herbivore relationships under eCO2 can function antagonistically and are highly context‐dependent, which poses a particular challenge. Still, we hypothesise as to the potential outcomes for AM fungal–plant–herbivore dynamics under eCO2 . We identify key research priorities to tackle the substantial gap in our understanding. If ecological theory is to effectively inform agricultural and natural management practices in the future, research needs to directly investigate how changes in global atmospheric CO2 concentrations impact the tripartite relationship between AM fungi, plants and insect herbivores. Aplain language summary is available for this article. Abstract : Plain Language Summary